COVID-19 Vaccine Acceptability in Dental Auxiliaries in Pakistan. are we Ready Yet - Aleeza Sana, Asma Shakoor, Hira Shafique, Yousaf Jamil, Hammad Hassan, Aleshba Saba Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study provides evidence of the willingness among dental auxiliaries to vaccine acceptance. The data will help in awareness and control of spread of COVID-19. Methodology: This descriptive cross-sectional survey was conducted from February 2021 to April 2021. The sample size was kept at 385, with 95 % confidence and 5% margin of error, out of which 340 responded. The sample population was selected via convenience sampling technique. Dental auxiliaries practicing within Pakistan for more than two years within an age range of 20 to 64, were included in the study. Descriptive statistics were used to summarize the questionnaire's responses, with the results being presented as frequencies and percentages and level of significance was set at P ≤ 0.05. Results: 340 dental auxiliaries participated in the study. 62.4% were in age range 18-34 years. 72.6% were males and 27.4% females.90% participants were educated till grade 11 or above. 66.2% participants were not willing to get vaccinated and 5.3% were not sure if they want it or not. Participants of older age groups were more hesitant in receiving vaccine. Conclusion: The findings of this research show high hesitancy rates for receiving COVID-19 vaccine among dental auxiliaries in Pakistan. Efforts should be made to educate people on scientific evidence basis and social media sites spreading misinformation should be banned.